2023
DOI: 10.3389/fcell.2023.1271575
|View full text |Cite
|
Sign up to set email alerts
|

Positioning SUMO as an immunological facilitator of oncolytic viruses for high-grade glioma

Paramesh V. Karandikar,
Lyle Suh,
Jakob V. E. Gerstl
et al.

Abstract: Oncolytic viral (OV) therapies are promising novel treatment modalities for cancers refractory to conventional treatment, such as glioblastoma, within the central nervous system (CNS). Although OVs have received regulatory approval for use in the CNS, efficacy is hampered by obstacles related to delivery, under-/over-active immune responses, and the “immune-cold” nature of most CNS malignancies. SUMO, the Small Ubiquitin-like Modifier, is a family of proteins that serve as a high-level regulator of a large var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 136 publications
0
2
0
Order By: Relevance
“…However, this case is emblematic because of the marked impact the tissue diagnosis has had on this patient's prognosis and management. Notably, other recent studies have also demonstrated that molecular information obtained from biopsies can guide potential treatment options, including the use of targeted inhibitors ( 12 15 ). Nonetheless, given the potential for complications and the incredible heterogeneity in the presentation of pontine glioneuronal masses, we suggest that the decision on whether to perform a biopsy should be based on the clinical judgment of risk and benefit by the surgeon and neuro-oncologist as well as shared decision-making with the patient.…”
Section: Discussionmentioning
confidence: 99%
“…However, this case is emblematic because of the marked impact the tissue diagnosis has had on this patient's prognosis and management. Notably, other recent studies have also demonstrated that molecular information obtained from biopsies can guide potential treatment options, including the use of targeted inhibitors ( 12 15 ). Nonetheless, given the potential for complications and the incredible heterogeneity in the presentation of pontine glioneuronal masses, we suggest that the decision on whether to perform a biopsy should be based on the clinical judgment of risk and benefit by the surgeon and neuro-oncologist as well as shared decision-making with the patient.…”
Section: Discussionmentioning
confidence: 99%
“…OV combination therapy is of increasing research interest [ 187 ]. Nassiri et al [ 147 ] tested a combination therapy of the oncolytic adenovirus DNX-2401 with a checkpoint inhibitor in a cohort of 49 patients with recurrent glioblastoma.…”
Section: Evolving Treatment Paradigms For Recurrent Glioblastomamentioning
confidence: 99%